Finite Element Method Using PDETOOL of Matlab for Hybrid Stepper Motor Design - E.V.C. Sekhara Rao; P.V.N. Prasad P.V.N. Prasad (Universitas Ahmad Dahlan, 2012)
This paper presents eight topologies design of permanent magnet hybrid (PMH) stepper motor for it’s magnetic circuit performance analysis using finite element method by PDETOOL of Matlab. The topologies are designed according to the number of stator teeth and length of airgap. This analysis is used to know mmf distribution due to permanent magnet and by exitation coil.This analysis helps to chose best design topology for better mmf distribution.